2011
DOI: 10.1111/j.1467-7687.2010.00968.x
|View full text |Cite
|
Sign up to set email alerts
|

An image is worth a thousand words: why nouns tend to dominate verbs in early word learning

Abstract: Nouns are generally easier to learn than verbs (e.g., Bornstein, 2005;Bornstein et al., 2004;Gentner, 1982;Maguire, Hirsh-Pasek, & Golinkoff, 2006). Yet, verbs appear in children's earliest vocabularies, creating a seeming paradox. This paper examines one hypothesis about the difference between noun and verb acquisition. Perhaps the advantage nouns have is not a function of grammatical form class but rather related to a word's imageability. Here, word imageability ratings and form class (nouns and verbs) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 69 publications
7
86
0
5
Order By: Relevance
“…Several studies have shown that words that are higher in imageability and concreteness tend to be learned earlier in acquisition (Gillette et al, 1999). McDonough et al (2011) found that imageability accounted for about 10% of the variance, after syntactic category (noun or verb) and frequency were partialed out. Their sample was limited to just 120 words that had imageability ratings, however.…”
Section: Concreteness and Imageabilitymentioning
confidence: 99%
“…Several studies have shown that words that are higher in imageability and concreteness tend to be learned earlier in acquisition (Gillette et al, 1999). McDonough et al (2011) found that imageability accounted for about 10% of the variance, after syntactic category (noun or verb) and frequency were partialed out. Their sample was limited to just 120 words that had imageability ratings, however.…”
Section: Concreteness and Imageabilitymentioning
confidence: 99%
“…Furthermore, several studies have reported imageability to facilitate word learning (Ma, Golinkoff, Hirsh-Pasek, McDonough, & Tardif, 2009;McDonough, Song, Hirsh-Pasek, Golinkoff, & Lannon, 2011;Tardif, 1996Tardif, , 2006. Imageability data have been collected for varying numbers of words in several languages, including English (Bird, Franklin, & Howard, 2001;Paivio et al, 1968;Stadthagen-Gonzalez & Davis, 2006), Chinese (Ma et al, 2009), French (Desrochers & Thompson, 2009), Italian (Della Rosa, Catricalà, Vigliocco, & Cappa, 2010) and Japanese (Nishimoto, Ueda, Miyawaki, Une, & Takahashi, 2012).…”
Section: Norwegian Words: a Lexical Database 281mentioning
confidence: 99%
“…For the 458 items that are common to Norwegian Words and the Norwegian CDI vocabulary checklist, Hansen (in progress) has calculated a CDI-based AoA for each word, defined as the first age in months when at least half of the children in the sample are reported by their parents to produce it (Goodman et al, 2008;Ma et al, 2009;McDonough et al, 2011). Sixteen of the words do not reach the 50% limit by 36 months; all of which have a subjective AoA of 4;6 or more.…”
Section: Subjective Age Of Acquisitionmentioning
confidence: 99%
“…This in turn should yield corresponding variations in maternal use of multimodal motherese to highlight noun-object versus verb-action relations to infants, especially because it scaffolds infants’ attention to word-referent relations. Given that referents for verbs are far more fleeting and intangible than referents for nouns (Gentner, 1982; McDonough, Song, Hirsh-Pasek, Golinkoff, et al, 2011), Indian mothers might use more scaffolding when speaking a verb-dominant Indian language than noun-dominant English.…”
Section: Introductionmentioning
confidence: 99%